A fossorial petalurid trace fossil from the Albian of Patagonia - Genise, Jorge Fernando (2020)
Maichnus wetkaroae igen. isp. nov., from the Albian of Patagonia, is composed of two or three ellipsoidal oblate chambers connected to shafts that show swellings and concentrically laminated linings. Such laminated linings are also present in chambers, and probably originated by radial backfilling and/or the successive discharges of liquid organic excretions. This unique morphology occurs in paleosols showing evidence of waterlogging. Trace fossil morphology and the occurrence of traces in clusters in waterlogged soils indicate that M. wetkaroae igen. isp. nov. represents larval burrows of fossorial petalurids. This is the first record of Odonatan trace fossils from paleosols and also the oldest one. M. wetkaroae igen. isp. nov. is one of the oldest insect trace fossils recorded from paleosols. It represents the first and unique paleontological evidence of the ancient origin of the burrowing behavior of petalurids postulated only theoretically until now in evolutionary scenarios of Odonata.